GAME ONLINE SEBAGAI GAYA HIDUP REMAJA KOS DI JALUR HIJAU MEDAN: ANALISIS PATOLOGI SOSIAL DALAM PERILAKU DIGITAL REMAJA - Sani Susanti; Clara Desmiati Br Sembiring; Elsy Virjitia; Liza Azzahrah; Seni Rasbina Br Karo Sekali (PT. Hasba Edukasi Mandiri, 2025)
The development of digital technology has brought significant transformations to the lifestyles of adolescents, particularly in their use of online games. This study aims to analyze how online games have become part of the lifestyle of boarding-house teenagers in the Jalur Hijau area of Medan, and how this behavior relates to digital social pathology. Using a qualitative approach through unstructured interviews with four boarding-house adolescents, the study found that online games function not only as entertainment but also as an alternative social space, a medium for escaping psychological pressures, and a means of forming self-identity. High playing intensity, discomfort when not playing, and neglect of important activities indicate symptoms of addictive behavior. The resulting social impacts include withdrawal from the surrounding environment, reduced face-to-face interactions, family conflicts, and digital consumerist behaviors such as top-ups. This study emphasizes that the phenomenon of online gaming in the lives of boarding-house adolescents has entered the realm of modern social pathology, which requires attention from families, academics, and the broader social environment.